Penerapan Model Pembelajaran Problem Solving dalam Meningkatkan Hasil Belajar IPA Kelas VIII UPTD SMP Negeri 2 Gunungsitoli - Febriani Zebua; Desman Telaumbanua; Hardikupatu Gulo (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research was motivated by the results of a preliminary study by researchers at SMP Negeri 2 Gunungsitoli, especially in Class VIII, it was found that the science learning process tends to utilize conventional learning models, student learning activities are lacking and the average score of student learning outcomes in the midterm exams is still in the low category. This study aims to describe the science learning process by applying the problem-solving learning model, describing student learning activities by applying the problem-solving learning model and describing student learning outcomes by applying the problem-solving learning model. The results showed: 1) The science learning process at SMP Negeri 2 Gunungsitoli in the 2022/2023 academic year by applying the Problem-Solving learning model in cycle I was 49.5% in the pretty good category and in cycle II it was 87% in the very good category. 2) student learning activities in cycle I obtained a percentage of 51.5% with the category quite active and in cycle II obtained a percentage of 89% with very active criteria. 3) Student learning outcomes in cycle I have an average value of 68.02 in the good category and a completeness percentage of 53%. In cycle II, student learning outcomes have an average score of 81.83 in the good category and a completeness percentage of 87%. Thus, the Problem-Solving learning model can improve student learning outcomes.